2003
DOI: 10.1002/cncr.11721
|View full text |Cite
|
Sign up to set email alerts
|

The significance of the Papanicolaou smear diagnosis of low-grade squamous intraepithelial lesion cannot exclude high-grade squamous intraepithelial lesion

Abstract: In this article, we consider the risk management for mid‐term planning of a global multi‐product chemical supply chain under demand and freight rate uncertainty. A two‐stage stochastic linear programming approach is proposed within a multi‐period planning model that takes into account the production and inventory levels, transportation modes, times of shipments, and customer service levels. To investigate the potential improvement by using stochastic programming, we describe a simulation framework that relies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
55
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 78 publications
8
55
1
2
Order By: Relevance
“…Some of these terminologies are: (1) LSIL with rare atypical cells suggestive of but not diagnostic for HSIL, (2) LSIL with ASC-H, (3) LSIL cannot exclude HSIL, (4) LASC-H, (5) LSIL-H, and (6) LSIL/ASC-H [1,2,4,5,6,7,12]. In the Zeynep Kamil Hospital Pathology Laboratory, in which the current study was conducted, these lesions are defined as LSIL/ASC-H. …”
Section: Discussionmentioning
confidence: 99%
“…Some of these terminologies are: (1) LSIL with rare atypical cells suggestive of but not diagnostic for HSIL, (2) LSIL with ASC-H, (3) LSIL cannot exclude HSIL, (4) LASC-H, (5) LSIL-H, and (6) LSIL/ASC-H [1,2,4,5,6,7,12]. In the Zeynep Kamil Hospital Pathology Laboratory, in which the current study was conducted, these lesions are defined as LSIL/ASC-H. …”
Section: Discussionmentioning
confidence: 99%
“…Hong et al [10] also reported a moderate degree of nuclear atypia, such as an increased N/C ratio, hyperchromasia and coarse chromatin, and a mild degree of nuclear membrane irregularity, among the most frequently encountered morphologic findings of these borderline cells. Nasser et al [5] described atypical squamous metaplastic cells (62%), atypical keratinized cells (20%) and dysplastic cells with a borderline N/C ratio (18%) as the cytological criteria of the cells that are suggestive but not diagnostic of HGSIL. Elsheikh et al [7] included rare dysplastic cells (usually <5 cells), atypical metaplastic squamous cells and cells with an intermediate N/C ratio between LGSIL and HGSIL as the criteria, and excluded atypical keratinized cells or keratinizing dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…The cytological diagnosis of LGSIL-H is typically entertained when a Pap smear demonstrates cells with definitive changes of LGSIL and a number of atypical cells that are suggestive but not diagnostic of HGSIL, and/or the Pap smear has borderline dysplastic cells that are between LGSIL and HGSIL [4,5,7,9]. The morphologic characteristics of these cells are not uniformly defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding supports the need for terminology that identifies this situation, so that women with LSIL who may have a higher-grade lesion receive colposcopies and possibly biopsies to exclude HSIL. Several studies [7][8][9][10][11] indicate that an LSIL-H interpretation has a higher likelihood of a cervical intraepithelial neoplasm 2 or 3 biopsy on follow-up than does LSIL alone.…”
Section: Overallmentioning
confidence: 99%